2010
DOI: 10.1111/j.1708-8305.2010.00462.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐Controlled Study Evaluating the Efficacy and Safety of Rifaximin for the Prevention of Travelers' Diarrhea in US Military Personnel Deployed to Incirlik Air Base, Incirlik, Turkey

Abstract: Rifaximin may represent an option among military personnel on deployment for prevention of TD with supportive future studies that consider deployment length, settings, and operational situations where widespread use of chemoprophylaxis may increase force health protection without undue risk during critical deployments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In terms of absolute risk reduction, pooled DerSimonian and Laird summary estimates found that rifaximin chemoprophylaxis decreased TD attack rates by a mean of 22.1% (95% CI: 6.3-37.9%) equating to a number needed to treat of 4.5 (95% CI: 2.6-15.9). With respect to rifaximin chemoprophylaxis, two studies (Armstrong et al ( 242 ) and Flores et al ( 243 )) did not show that chemoprophylaxis with rifaximin reached a statistically signifi cant diff erence in preventing TD compared with placebo ( 242,243 ). In both studies the incidence of TD in the control group was relatively low (8/48 or 17% and 9/47 or 19%, respectively), which could have explained the fi ndings given sample size calculations were based on the expected incidence of TD to be 40%, and thus recruitment may have been too small to detect the true eff ect of rifaximin in preventing TD.…”
Section: Prophylaxismentioning
confidence: 99%
“…In terms of absolute risk reduction, pooled DerSimonian and Laird summary estimates found that rifaximin chemoprophylaxis decreased TD attack rates by a mean of 22.1% (95% CI: 6.3-37.9%) equating to a number needed to treat of 4.5 (95% CI: 2.6-15.9). With respect to rifaximin chemoprophylaxis, two studies (Armstrong et al ( 242 ) and Flores et al ( 243 )) did not show that chemoprophylaxis with rifaximin reached a statistically signifi cant diff erence in preventing TD compared with placebo ( 242,243 ). In both studies the incidence of TD in the control group was relatively low (8/48 or 17% and 9/47 or 19%, respectively), which could have explained the fi ndings given sample size calculations were based on the expected incidence of TD to be 40%, and thus recruitment may have been too small to detect the true eff ect of rifaximin in preventing TD.…”
Section: Prophylaxismentioning
confidence: 99%
“…First, we chose one of the most common AR structures in the behavioral sciences, an AR model of order 1 with two sample size configurations: (1a) T = 100, N = 1, a configuration commonly utilized in the time series literature to evaluate finite-sample performance of statistical approaches; and (1b) T = 14, N = 100, as commonly seen in many ILD studies in psychology (Armstrong et al, 2010;Beidel, Neal, & Lederer, 1991;Roche et al, 2016;Steger & Frazier, 2005). Second, we simulated a complex AR structure with sharp shifts using a seasonal autoregressive integrated moving average (SARIMA; with N = 100, T = 14) (Box & Jenkins, 1976;Box et al, 2013;Brockwell & Davis, 2002;Reinsel, 2003).…”
Section: Simulation Studymentioning
confidence: 99%
“…1 In special circumstances, rifaximin is the drug of choice for prophylaxis in travelers who could not tolerate an infection due to comorbidities or other practical reasons (eg, sports figures). [40][41][42][43][44] There is solid evidence to support the use of rifaximin in acute diarrhea. In a study on 210 Americans aged 18 years or older traveling to Mexico (diarrhea -producing E. coli as a major pathogen causing TD), 14 participants received rifaximin (200 mg/d, 200 mg twice daily, or 200 mg 3 times daily) or placebo for 2 weeks.…”
Section: Postinfectious Irritable Bowel Syndromementioning
confidence: 99%